FRI0390 European multicentre study validates elf test as biomarker of fibrosis in systemic sclerosis. (15th June 2017) - Abignano, G; Blagojevic, J; Bissell, L-A; Dumitru, RB; Eng, S; Allanore, Y; Avouac, J; Bosello, S; Denton, C; Distler, O; Ferraccioli, G; Jordan, S; et al.
Abstract : Background: The Enhanced Liver Fibrosis (ELF) test is a serum test including the serum concentrations of amino-terminal pro-peptide of procollagen type III (PIIINP), tissue inhibitor of matrix metalloproteinase-1 (TIMP-1) and hyaluronic acid (HA). A recent single centre study showed that ELF score and its components are markers of overall fibrosis in systemic sclerosis (SSc) mainly reflecting skin and lung involvement (1). Objectives: To determine the value of ELF score and its single analytes in an independent multicentre cohort of SSc patients. Methods: 254 SSc patients from 6 European Rheumatology Centres were included in this study. Clinical data were collected at time of sampling. Serum samples were collected and stored according to EUSTAR biobanking recommendations (2). Sera were analysed employing a high-throughput in vitro diagnostic (Siemens Alpha-Centaur). Statistical analysis was performed with SPSS software V.24. Results: The 254 SSc patients had a mean age 55.8±13.8 years, and included 209 females and 80 patients with diffuse cutaneous SSc (dcSSc). ELF score was overall higher in males than in females (p=0.0236) as well as in dcSSc compared to limited cutaneous SSc patients (p=0.0015). ELF score and the single markers significantly correlated with the degree of skin involvement (mRSS) and inversely correlated with FVC%, TLC% and DLCO%. Concordantly all markers significantly correlated with skin and lung severity as assessed by the Medsger's scale (Table 1 ). TIMP-1 and PIIINP levels were higher in patients with lung fibrosis assessed by chest HRCT scan (p=0.0126 and p=0.0308 respectively). Significant correlation (p<0.0001) was found between ELF score, TIMP-1, PIIINP, HA and total disease severity and activity. Multivariate analysis indicated that age (p<0.0001), mRSS (p<0.0001) and DLCO% (p=0.005) were independently associated with ELF score. Conclusions: The value of ELF score as independent marker of skin and lung involvement is confirmed in a second independent multicentre cohort of SSc patients. A longitudinal study paired with analysis of large cohort of healthy controls is currently on going to identify a SSc specific test with the highest predictive value for skin and lung progression independently of age and gender. References: Abignano G et al. Ann Rheum Dis. 2014. Beyer C et al. Ann Rheum Dis. 2011. Disclosure of Interest: None declared